Answer:
n = -2
Step-by-step explanation:
4n + 12 = 4
Subtract 12 from both sides.
4n = -8
Divide both sides by 4.
n = -2
Answer:
Step-by-step explanation:
I don't really know sorry I am not smart I only sign up to see the answers
Answer:
The answer is B.
Step-by-step explanation:
when x is 0, y is 5. So that is the yintercept and 4-5=-1 -4-0=-4 do 1/4
Answer:
Elimination method
Step-by-step explanation:
We have a choice to eliminate the y or x:
I chose x
So now we double the second equation to make the co efficient of x the same:
6x-5y = -3
6x+4y = 24
Now we subtract both equations to eliminate the x's:
6x-5y = -3
- - -
6x+4y = 24
-9y = -27
y = 3
Now we substitute this value into either equation 1 or 2:
I chose 2
3x + 2(3) =12
Simplify:
3x + 6 =12
Subtract 6 from both sides:
3x + 6 -6 = 12 -6
Simplify:
3x = 6
Divide both sides by 3:
3x÷3 = 6÷3
Simplify:
x = 2
Answer:
2
Step-by-step explanation: